Hybrid Opioid/Non-Opioid Ligands in Pain Research - Kleczkowska, Patrycja; W. Lipkowski, Andrzej; Tourwe, Dirk; Ballet, Steven (Current Pharmaceutical Design, 2013)
To address the different types of pain (e.g. acute, chronic, neuropathic) different classes of medications, mainly non-steroidal anti-inflammatory drugs and narcotics (opioids), are used. More specifically, the alleviation or treatment of moderate to severe pain states commonly invokes the use of opioids. Unfortunately, their chronic administration induces various undesirable side effects, such as for example physical dependence and tolerance. One strategy to overcome these major side effects and to prolong the antinociceptive efficiency of the applied drugs involves the creation of multifunctional compounds which contain hybridized structures. Combination of opioid agonist and antagonist pharmacophores in a single chemical entity has been considered and extensively investigated, but opioids have also been combined with other bioactive neurotransmitters and peptide hormones that are involved in pain perception (e.g. substance P, neurotensin, cholecystokinin, cannabinoids, melanocortin ligands, etc.). Such novel chimeras (also called designed multiple ligands or twin/triplet drugs), may interact independently with their respective receptors and potentially result in more effective antinociceptive properties. The designed multiple ligands presented in this work include opioid-non-opioid peptide dimer analogs, mixed peptidic- non-peptidic bifunctional ligands and dual non-peptidic dimers. The main focus herein is placed on the design and biological evaluation of these multiple opioid compounds, rather than the synthetic approach and preparation.
Keywords: bi- or multifunctional compounds